Anaesthesia mumps after total laparoscopic hysterectomy under general anaesthesia - Udayakumar, Prabha; Mani, Kanmani; P., Hemaamallene (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Anaesthesia mumps is a rare clinical entity characterised by acute transient swelling of the parotid gland in postoperative period. In our case a 58 years obese lady developed left sided parotid swelling which was managed conservatively and settled without any sequelae. In this article we discuss possible causes, differential diagnosis and treatment for this condition. This is to increase awareness about this relatively unknown condition amongst anaesthetist and surgeons and to avoid unnecessarily apprehension in post-operative period.